Pengaruh Globalisasi Budaya Korea terhadap Pengembangan Wisata di Bandung: Analisis Sosial dan Ekonomi - Pratama, Obi (Al-DYAS, 2025)
This research is motivated by the enthusiasm of many people who like Korean culture, including Korean-themed tourism, so that it has an impact on the economy and society. The purpose of this study is to analyze the influence of Korean cultural globalization on the tourism sector in Bandung using a mixed method approach. The quantitative method was conducted through a survey of 300 domestic tourists interested in Korean culture, to identify their preferences regarding K-pop, K-drama, K-food, and social media in tourism decision-making. Meanwhile, the qualitative method was applied through in-depth interviews with 15 tourism business actors involved in the Korean culture-based industry in Bandung. The results show that tourists' preferences for Korean culture, especially K-pop, K-drama, and K-food, play a big role in attracting tourists to visit the city. The existence of Korean restaurants, cafes with K-pop nuances, and shopping malls that offer Korean products further enrich the tourist experience. Social media also has a huge role in introducing and promoting Korean culture-based tourist attractions, which directly influences tourists' decisions in choosing Bandung as their travel destination. The positive impact of this phenomenon on the economy of Bandung is very felt, especially in the culinary, entertainment, and retail sectors based on Korean culture. Similarly, the entertainment and retail sectors that offer Korean products also recorded steady growth. The main conclusion of the study is that Korean culture, especially K-pop and K-drama, plays a significant role in attracting tourists to Bandung and this is strengthened by the existence of social media. The implications of this research are one of the recommendations for the government, tourism actors and also others as a reflection and illustration of the influence of Korean culture on the social and economic community.